Loop-mediated isothermal amplification-microfluidic chip for the detection of Trichophyton infection - Jiang, Weiwei; Hu, Dongying; Xu, Yanyan; Chen, Yang; Zhu, Xiaoyang; Han, Zhao; Ye, Xin; Li, Xiaojing (Frontiers in Microbiology, 2022)
Trichophyton is the most pathogenic type of fungal skin infection. It often invades and grows in a keratin-rich matrix, and lesions include human skin, hair, and fingernails (toenails). We designed LAMP primers for Trichophyton and developed a LAMP-Microfluidic chip detection system for Trichophyton. This system detects six common species of Trichophyton in the genus Trichophyton, including Trichophyton rubrum, Trichophyton mentagrophyte, Trichophyton violaceum, Trichophyton tonsurans, Trichophyton verrucosum, and Trichophyton schoenleinii. The specificity reached 100%, and the sensitivity could reach about 1 × 102 copies/μl. The entire detection process can be completed within 60 min and does not cross-react with other dermatophytes. The established LAMP-Microfluidic chip detection system has the advantages of simple operation, high specificity, and high sensitivity, and has the potential for clinical application.